Nanoenergy Nanotechnology Applied for Energy Production (Springer International Publishing, 2018)
This book discuss the recent advances and future trends of nanoscience in solar energy conversion and storage. This second edition revisits and updates all the previous book chapters, adding the latest advances in the field of Nanoenergy. Four new chapters are included on the principles and fundamentals of artificial photosynthesis using metal transition semiconductors, perovskite solar cells, hydrogen storage and neutralization batteries. More fundamental aspects can be found in this book, increasing the comparison between theory-experimental achievements and latest developments in commercial devices.